Studi Evaluatif Terhadap Laporan Perbankan Syariah - Rifqi Muhammad (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2009)
Islamic banking is the fastest-growing segment of world finance. Islamic Banks should ideally operate in accordance with the principles laid down by Islamic law (Shariah). One of the main sources to analyze and evaluate the activities of Islamic banks is annual report. Annual report is the way to disclose financial and non-financial performance of Islamic banks. This paper aims at elaborating the sources of development of Islamic banking reporting based on the AAOIFI (Accounting and Auditing Organization for Islamic Financial Institutions) standards, alternatives of Islamic corporate reporting, and the accounting policies of Islamic banks in many countries. Secondly, this paper tries to formulate the components should be reported by Islamic banks in order to increase the degree of accountability. Thirdly, this paper also tries to evaluate the existing Islamic banking reporting components in order to measure the gap between expectations and realities. This study finds that Islamic banks do not have similarity in disclosing financial and non-financial activities and performances. However, this diversity model can be complementary one another towards ideal Islamic banking reporting. Keywords: Islamic bank, Islamic accounting, Islamic corporate report, Islamic accountability